Improving the safety and quality of fermented shrimp paste (terasi) through supplementation of betel leaf (Piper betle L.) essential oil - Surya, Reggie; Santos, Reinaldo Socorro (Hasanuddin University Food Science and Technology Study Program, 2024)
Terasi is a traditional fermented shrimp paste that has been an integral part of Indonesian cuisine and food culture. Despite its broad use and complex distinctive flavor, shrimp paste could be harmful for human consumption, particularly when its quality has deteriorated. Indeed, many chemical reactions and microbial activities taking place during shrimp paste fermentation could lead to a decrease in quality and the formation of toxic compounds that are potentially injurious to human health. Thus, this study aimed to explore to improve the safety and quality of shrimp paste by incorporating betel leaf (Piper betle L.) essential oil, known to exert antioxidant and antimicrobial properties. The supplementation of betel leaf essential oil (1% and 5%) reduced lipid peroxidation as well as the formation of toxic compounds, including histamine and acrylamide in the shrimp paste fermented for 30 and 60 days. This phenomenon was associated with the inhibition of microbial growth in shrimp paste supplemented with betel leaf essential oil. The sensory analysis revealed that the supplementation of 1% betel leaf essential oil did not affect the consumer’s preference for shrimp paste. Therefore, the present study highlights the potential of betel leaf essential oil as a food additive to improve the safety and quality of fermented shrimp paste.